Invitation ? RMCMI 1997 ? 1998 Board of Directors (Rocky Mountain Coal Mining Institute, 1997)
Thomas J. LIEN RMCMI PRESIDENT 1997-1998 on behalf of the RMCMI Board of Directors and Officers of The Rocky Mountain Coal Mining Institute cordially invites you and your family to attend the 94TH Regular Meeting and Convention to be held June 27 thru June 29, 1998 Snowmass Village, Colorado